Disentangling India's Investment Slowdown - Anand, Rahul (IMF Working Papers; Working Paper ;, 2014)
This paper documents the recent slowdown in investment in India and explores its underlying causes. The sharp investment deceleration has sparked an intense debate about the role of interest rates, as well as business confidence and economic policy uncertainty. Our results suggest that while explaining aggregate investment activity better than nominal interest rates, real interest rates account for only one quarter of the explained investment downturn. In addition, standard macro-financial variables do not fully explain the recent investment slump. Using a new measure of economic policy uncertainty, the results suggest that heightened uncertainty and deteriorating business confidence have played a key role in the recent investment slowdown.